Association of long-term triglyceride-glucose index level and change with the risk of cardiometabolic diseases - Xu, Wenqi; Zhao, Haiyan; Gao, Lishu; Guo, Lu; Liu, Jianrong; Li, Haixia; Sun, Junyan; Xing, Aijun; Chen, Shuohua; Wu, Shouling; Wu, Yuntao (Frontiers in Endocrinology, 2023)
Abstract: Objective: The triglyceride-glucose (TyG) index is considered as a pivotal factor for various metabolic, cardiovascular, and cerebrovascular diseases. However, there is currently a paucity of relevant studies on the association between long-term level and change of TyG-index and cardiometabolic diseases (CMDs) risk. We aimed to explore the risk of CMDs in relation to the long-term level and change of TyG-index. Methods: Based on the prospective cohort study, a total of 36359 subjects who were free of CMDs, had complete data of triglyceride (TG) and fasting blood glucose (FBG) and underwent four health check-ups from 2006 to 2012 consecutively were followed up for CMDs until 2021. The associations between long-term level and change of TyG-index and CMDs risk were assessed by Cox proportional hazards regression models to compute hazard ratios (HRs) and 95% confidence intervals (CIs). The TyG-index was calculated as ln [TG, mg/dL) × FBG, mg/dL)/2]. Results: During the median observation period of 8 years, 4685 subjects were newly diagnosed with CMDs. In multivariable-adjusted models, a graded positive association was observed between CMDs and long-term TyG-index. Compared with the Q1 group, subjects with the Q2-Q4 group had increased progressively risk of CMDs, with corresponding HRs of 1.64(1.47-1.83), 2.36(2.13-2.62), 3.15(2.84-3.49), respectively. The association was marginally attenuated, after further adjustment for the baseline TyG level. In addition, compared with stable TyG level, both loss and gain in TyG level were associated with increased CMDs risk. Conclusions: Long-term elevated level and change of TyG-index are risk factors for the incident CMDs. Elevated TyG-index in the early stage remains to exert cumulative effects on the occurrence of CMDs even after accounting for the baseline TyG-index.